2013
DOI: 10.1007/s00424-013-1298-9
|View full text |Cite
|
Sign up to set email alerts
|

The phosphate transporter NaPi-IIa determines the rapid renal adaptation to dietary phosphate intake in mouse irrespective of persistently high FGF23 levels

Abstract: Renal reabsorption of inorganic phosphate (Pi) is mediated by the phosphate transporters NaPi-IIa, NaPi-IIc, and Pit-2 in the proximal tubule brush border membrane (BBM). Dietary Pi intake regulates these transporters; however, the contribution of the specific isoforms to the rapid and slow phase is not fully clarified. Moreover, the regulation of PTH and FGF23, two major phosphaturic hormones, during the adaptive phase has not been correlated. C57/BL6 and NaPi-IIa(-/-) mice received 5 days either 1.2 % (HPD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 62 publications
(84 reference statements)
6
31
0
Order By: Relevance
“…NaPi-IIa expression and FePO 4 2 increased to the same extent in proteinuric rats subjected to a normal-or a high-phosphate diet, indicating that adaptation to a highphosphate diet is not fully impaired because it may not rely only on FGF-23. 34 We observed that after a phosphate load, control rats did not display residual apical NaPi-IIa labeling by immunofluorescence ( Figure 3F). In phosphate-loaded proteinuric rats, NaPi-IIa was also less apparent at the apical membrane but could still be seen in some proximal tubule S1 segments of the juxtamedullary region ( Figure 3F).…”
Section: Albuminuria Is Associated With Higher Plasmamentioning
confidence: 80%
“…NaPi-IIa expression and FePO 4 2 increased to the same extent in proteinuric rats subjected to a normal-or a high-phosphate diet, indicating that adaptation to a highphosphate diet is not fully impaired because it may not rely only on FGF-23. 34 We observed that after a phosphate load, control rats did not display residual apical NaPi-IIa labeling by immunofluorescence ( Figure 3F). In phosphate-loaded proteinuric rats, NaPi-IIa was also less apparent at the apical membrane but could still be seen in some proximal tubule S1 segments of the juxtamedullary region ( Figure 3F).…”
Section: Albuminuria Is Associated With Higher Plasmamentioning
confidence: 80%
“…However, there are conflicting data regarding the sequence of events triggered by high dietary Pi as well as the nature of the trigger itself. PTH may have a key role in the acute renal response, with other hormones coming into play only later on, 23,[32][33][34] but the presence of yet-unidentified intestinal factor(s) stimulating renal Pi excretion independent from PTH has been proposed. 22 Here, we administered a Pi load to rats both intravenously (to bypass the gastrointestinal tract) and intragastrically and compared the acute responses in intact and PTX animals.…”
Section: Discussionmentioning
confidence: 99%
“…PTH values showed a high degree of intragroup variability. We reported recently that the levels of this hormone change very quickly in response to switches in dietary P i (8). At the end of the sucrose/Doxydrinking protocol, animals were housed in single metabolic cages and food intake was closely monitored.…”
Section: Napi-iia Actinmentioning
confidence: 99%